THE RELATIONSHIP BETWEEN ARM MUSCLE STRENGTH AND FOREHAND SMASH ABILITY IN STUDENTS' TABLE TENNIS GAMES - Suwo, Rahedin; Yasin, Restika Apridilla; Wardhani, Rio (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research is important because table tennis is a sport that requires fine motor coordination and good arm-muscle strength to play effectively. The method used is the correlational method. The research sample consisted of 30 male students at SMP Negeri 3 Kolaka in table tennis extracurricular lessons. Data was collected through arm muscle strength tests using table tennis's push-up test and forehand smash ability tests. Next, the data was analyzed using descriptive statistics to identify the level of arm muscle strength and forehand smash ability and Pearson correlation analysis to evaluate the relationship between the two. The results showed that most students had different levels of arm muscle strength and forehand smashes also varied among the student sample. The results of Pearson correlation analysis showed that there was a significant positive relationship between arm muscle strength and forehand smash ability in table tennis (r = 0.878, p < 0.05). This indicates that the stronger a person's arm muscles, the better his forehand smash ability. The results can reinforce designing more effective training programs to increase arm muscle strength and forehand smash ability in table tennis. Apart from that, this research can also help identify potential talents in the field of table tennis at SMP Negeri 3 Kolaka